Main Targets of Interest for the Development of a Prophylactic or Therapeutic Epstein-Barr Virus Vaccine - Jean-Pierre, Vincent; Lupo, Julien; Buisson, Marlyse; Morand, Patrice; Germi, Raphaële (Frontiers in Microbiology, 2021)
Epstein-Barr virus (EBV) is one of the most widespread viruses in the world; more than 90% of the planet’s adult population is infected. Symptomatic primary infection by this Herpesviridae corresponds to infectious mononucleosis (IM), which is generally a benign disease. While virus persistence is often asymptomatic, it is responsible for 1.5% of cancers worldwide, mainly B cell lymphomas and carcinomas. EBV may also be associated with autoimmune and/or inflammatory diseases. However, no effective treatment or anti-EBV vaccine is currently available. Knowledge of the proteins and mechanisms involved in the different steps of the viral cycle is essential to the development of effective vaccines. The present review describes the main actors in the entry of the virus into B cells and epithelial cells, which are targets of interest in the development of prophylactic vaccines aimed at preventing viral infection. This review also summarizes the first vaccinal approaches tested in humans, all of which are based on the gp350/220 glycoprotein; while they have reduced the risk of IM, they have yet to prevent EBV infection. The main proteins involved in the EBV latency cycle and some of the proteins involved in the lytic cycle have essential roles in the oncogenesis of EBV. For that reason, these proteins are of interest for the development of therapeutic vaccines of which the objective is the stimulation of T cell immunity against EBV-associated cancers. New strategies aimed at broadening the antigenic spectrum, are currently being studied and will contribute to the targeting of the essential steps of the viral cycle, the objective being to prevent or treat the diseases associated with EBV.